Perhitungan Desain Konsep Reaktor Cepat Berpendingin Karbondioksida Superkritis dan Berbahan Bakar Uranium Metalik Alam - Via Vionita; Fiber Monado; Menik Ariani; Idha Royani (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
This study discusses the design concept of the fast reactor core with supercritical carbon dioxide as coolant and natural metallic uranium as fuel that has been burnup for one hundred years. Calculations and simulations are performed using the SRAC code. The PIJ-SRAC module is for calculating the fuel cell level, and the CITATION-SRAC module is for calculating the reactor core level. Radial modified CANDLE is applied as a fuel arrangement strategy in the reactor core. The survey parameters were calculated in the form of burnup level, infinite multiplication factor (kinf), the density of fissile and fertile atoms, conversion ratio, and ef ective multiplication factor (kef ). The calculated reactor core thermal power varies from 400 MWt, 450 MWt, and 500 MWt. Based on calculation and simulation results, a reactor with thermal power of 450 MWt with geometry RZ (R = 150 cm and Z = 150 cm) is the best design. The calculation results show that the kef value from the beginning of the combustion cycle is around 1.002662 with a reactivity value of 0.2654%; until the end of the cycle, the kef value is 1.041057 with a reactivity value of 3.9437%.